(untitled) (Conference Zone, 2022)
. Республике Uzbekistan inclusion is considered as one of the strategic objectives of the development of the education system. The central role assigned to the teacher in the modernization and reform of modern education necessitates qualitative changes in the training of specialists in the field of inclusive education.